The Effect Of Service Excellence And Brand Image On Customer Satisfaction And Loyalty In Shopee Delivery Service Users In KC Kediri - Lubis, Khoirul Auliya; Mulyati, Erna (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
The success of delivery services in the e-commerce ecosystem is no longer determined solely by the speed of distribution, but by the ability of service providers to build a positive perception and consistent service experience in the eyes of customers. In the context of PT Pos Indonesia's partnership with the Shopee platform, this study examines how service quality and brand image contribute to the formation of customer satisfaction and its impact on the dedication of delivery service users at the Kediri Branch Post Office. This research was designed with a quantitative approach through a survey of 300 respondents who were selected purposively based on the experience of Shopee delivery service users. Primary data was obtained through a questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) which was processed using SmartPLS4 software. Obtained from the results of deepening the material that refers to service quality and brand image, it plays a significant role in increasing customer satisfaction. Customer satisfaction has proven to be a major driver in supporting the loyalty of delivery service users. In addition, the quality of service has a direct contribution to customer retention, and the brand image does not show an essential direct impact. Nonetheless, customer satisfaction serves as an effective link in bridging the impact of service quality and brand image on customer loyalty. These findings confirm that the service quality improvement strategy that refers to customer experience is an important component to strengthen loyalty to e-commerce-based delivery services at the Kediri Branch Post Office.